In vitro effects of rituximab on the proliferation, activation and differentiation of human B cells. - Kamburova, E; Koenen, H; Boon, L; Hilbrands, L; Joosten, I (2012)
Rituximab is a chimeric anti-CD20 monoclonal antibody (mAb) used in B-cell malignancies, various autoimmune disorders and organ transplantation. Although administration of a single dose of rituximab results in full B-cell depletion in peripheral blood, there remains a residual B-cell population in secondary lymphoid organs. These nondepleted B cells might be altered by exposure to rituximab with subsequent immunomodulatory effects. Therefore, we analyzed in vitro the effects of rituximab on proliferation, activation and differentiation of CD19(+) B cells by means of carboxyfluorescein succinimidyl ester (CFSE)-based multiparameter flow cytometry. Rituximab inhibited the proliferation of CD27(-) naïve, but not of CD27(+) memory B cells. Interestingly, upon stimulation with anti-CD40 mAb and interleukin-21 in the presence of rituximab there was an enrichment of B cells that underwent only one or two cell divisions and displayed an activated naïve phenotype (CD27(-)IgD(+)CD38(-/+)). The potency of prestimulated B cells to induce T-cell proliferation was increased by exposure of the B cells to rituximab. Of note, after stimulation with rituximab-treated B cells, proliferated T cells displayed a more Th2-like phenotype. Overall, these results demonstrate that rituximab can affect human B-cell phenotype and function, resulting in an altered outcome of B-T cell interaction.